Ecology of Knowledge in the Context of the Implementation of Climate Change Adaptation Measures in Developing Countries - Dias Pereira, Guilherme; Simões, André Felipe (Environmental Management and Sustainable Development, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Climate change involves a series of transformations in the synoptic systems of the planet. Its effects are not equitable, so the onus falls on the most vulnerable. Countries considered to be developing tend to be more vulnerable and therefore need to implement adaptation measures. However, these measures are not always viable within the social, environmental, institutional, geophysical, and economic dimensions, especially in the latter. Developing countries often need funding from international multilateral networks to make adaptation measures viable. Yet, projects that receive financing usually reproduce colonial aspects by erasing local knowledge, as in the case of measures implemented in São Tomé and Príncipe, and Bhutan. The essence of the ecology of knowledge concept can be a way for local knowledge to be valued and to be part of adaptation measures projects in countries considered to be developing.